Analysis of the Narrative and Its Connection with the Theme in Cheraghha Ra Man Khamoosh Mekonam - Timoor Malmir; Hosein Asadijozani (مطالعات زبانی و بلاغی)
Cheraghha Ra Man Khamoosh Mekonam (I Will Turn off the Lights) is Zoya Pirzad's debut novel revolving on the theme of loneliness and the boredom ensuing from this loneliness. This research is a descriptive-analytical investigation of Zoya Pirzad’s Cheraghha Ra Man Khamoosh Mekonam concerning the narrative and its connection with the theme. The popularity and consecutive editions of the novel prompted us to evaluate this novel in terms of selection and appropriateness of elements such as narrator, point of view, focalization, order, duration and frequency and theme. Our main purpose is to explain the author's level of innovation in using fictional elements and to explain the relationship between narrative and theme of the novel. Due to the lack of dramatization of the text, the narrator mixes up the present time of narration with the time of occurrence of the events. The direct delivery of information to the audience is one of the signs of this fusion. The weakness of authorship is revealed in the construction of the narrative. The writer has also chosen a traditional narrative construction and finally created a simple and straightforward plot which has no sign of a new perspective. Exploring order, duration and frequency shows that the narrative of the novel is one of the classical and traditional narrative types. Due to the slow narrative pace, the author has not been able to represent the theme of the novel in a deep and artistic way.